THE INFLUENCE OF INNOVATIVENESS ON THE WORK PERFORMANCE OF PHYSICS TEACHER IN THE STATE SENIOR HIGH SCHOOL AT BENGKULU PROVINCE - Connie, Connie; Zuki, Arieldo Meizul (Universitas Ahmad Dahlan, 2020)
The objective of this research was to analyze the influence of the innovativeness of physics teachers on the work performance of physics teachers in the state senior high school at Bengkulu province. This research was conducted by surveying physics teachers in the state high school at Bengkulu province with a sample of 90 teachers of physics, were selected by using a simple random sampling technique. Data has been analyzing by using the â€œpath analysis methodâ€ with Microsoft Excel and SPSS 17 as researchâ€™s computing tools. The results concluded that there is a direct, positive, and significant influence of professional competency, work motivation, and innovativeness of physics teachers toward the work performance of the physics teacher. And the professional competency and the work motivation of the physics teacher have an indirect, positive, and significant influence on the work performance of physics teachers through the innovativeness of the physics teacher itself.